Burnt ash from Hazardous Prosopis Juliflora Plant as a Pozzolanic replacement Material in Cement - V.S. Sethuraman, L. K. Rex, Gomathi Nagajothy (International Journal of Advanced Science and Technology, 2020)
Concrete is the indispensable material used in construction field. Concreting in the recent part has resulted in degradation of the environment and ecosystem. Prosopis Juliflora is one of the harmful plants, which causes reduction in moisture content in air and ground water table. In this study Prosopis Juliflora Plant ash has been tested as a partial replacement of cement due to presence of calcium content. The percentage of replacement of cement by Prosopis Juliflora plant ash was tested between 0 to 100%. Concrete specimens including cubes, cylinders and prisms were cast and tested for 7, 14, 28 days compressive strength, split tensile strength and flexural strength. These test results revealed that the optimum replacement of cement by Prosopis Juliflora plant ash was found to be effectivebetween5% to 20%.From the experimental investigation, it was observed that the partial replacement of cement by plant ash in concrete had significant improvement in terms of strength when compared to concrete made with cement. Keywords:  Concrete, Prosopis Juliflora, Compressive Strength, Split Tensile Strength, Flexural Strength